TSMA: uma arquitetura para gerenciar a sinalização de trânsito - Lira, Everton Rocha (2016)
This academic work consists of specifying and evaluating TSMA (Traffic Sign Management Architecture), an architecture that is being proposed to address limitations of the current traffic sign infrastructure. A large-scale implementation of TSMA would allow, for instance, that remote updates sent to traffic signs be used to divert the traffic flow in case of accidents or even change the limit speed of certain roads during the rush hours. TSMA-compliant vehicles have a receiver unit that displays traffic signs to the driver in the navigation system display; this feature brings into evidence the traffic signs and could potentially reduce the risk of accidents being caused by driver inattention. This work follows a global intelligent cities trend by which systems involved in peoples routines are interconnected and adapt to their needs to better provide comfort and safety. Simulations were run to test the architecture s usage scenarios and a communication prototype was developed as part of this effort. Results obtained from experiments using this prototype and the simulated scenarios confirmed the positive expectations regarding TSMA s viability and efficiency.